Al-Sharī’ah al-Islāmīyah fī ‘Aṣr al-Amrikazīyah al-Iqlīmīyah bi Indūnīsīya - Huda, Yasrul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
This article covers the efforts being made by two regions of Indonesia to implement Islamic law, that is, Aceh and West Sumatra. As one of the Special Autonomous Regions in Indonesia, Aceh has far greater freedom and authority to make its own rules and regulations, which includes the use of Islamic law as the rule of law in the area. In order to achieve this objective, the government of Aceh has introduced a regulation regarding the implementation of Islamic law and is quite extensive in that it covers aqidah (Islamic beliefs), ibadah (matters of worship), muamalah (dealings between people), akhlak (character), pendidikan (education), dakwah, baitul mal (the treasury), kemasyarakatan (social matters), syiar Islam (Islamic propogation), pembelaan Islam (defending Islam), peradilan (judicature), jinayat, munakahat (marriage) and waris (inheritance). This means that Islamic law should in theory govern almost all aspects of Islamic law and daily life.DOI: 10.15408/sdi.v13i3.560